Self-Efficacy of the University Students’ TOEFL Performance: Differences in the Test Skill and English Skills in TOEFL - Yoestara, Marisa; Putri, Zaiyana (Jurnal Ilmiah Peuradeun, 2020)
This study aimed at reporting differences in terms of the university students’ TOEFL self-efficacy in the test skill and the English skills tested in TOEFL namely listening, structure, and reading. In conducting the study, the explanatory sequential mixed method was used as the study design, where the quantitative data from the survey was conducted first followed by the follow-up interview as the qualitative data. To collect the data in this study, a specifically designed self-efficacy questionnaire of TOEFL was distributed to the total sample of 200 university students across different disciplines from Syiah Kuala University and the University of Serambi Mekkah. The interview was then conducted with 3 selected students to have a deeper understanding of the study result. In terms of the data analysis, one-way ANOVA and t-test were used to describe the quantitative data, while the qualitative data was described and elaborated in words with detailed explanations. The result showed that there was a significant difference among the test skill and the English skills in TOEFL, where F= 13.61 (3, 796), p<0.05. The result also revealed that within the gender, only reading skill had a significant difference, where t198= -2.003, p <. 005, and within the language course participation, all the test skills and TOEFL skills were significantly different as the p-value of each skill was smaller than .005 (p< .005).